The Potential of Beeswax Coating in the Preservation of Tomato (Solanum lycopersicum) Fruits - T. Banjo; R. Malomo (Journal of Food Quality and Hazards Control, 2024)
Background: Tomatoes are fruits that are highly prone to spoilage, making them vulnerable to microbial decay. This research aimed to explore the effectiveness of an edible coating, specifically beeswax, in prolonging the shelf-life of tomato fruits. Methods: A total of twenty-four tomatoes were procured from the market in September 2021, washed, and subsequently treated with beeswax at varying concentrations of 3, 6, 9, 12, and 15%) (w/v). The tomatoes were then stored in well-ventilated baskets for 30 days, during which organoleptic, biochemical, and microbial assessments were conducted. The Gas Chromatography-Mass Spectrometry analysis of the beeswax samples was performed following standard procedures. The relative percentage of each component was determined by comparing its average peak area to the total area. The mean and standard deviation of the duplicated data were calculated, and significance was assessed using ANOVA at a 95% confidence interval (p-value<0.05) with the aid of the Statgraphics Plus (version 5.0) statistical package. Results: The beeswax emulsion achieved an optimal preservation rate of 70%, significantly higher than the control group, which had a rate of 20%. Additionally, a mean preservation rate of 68% was noted with the 12% beeswax emulsion, compared to 20% for control after 30 days. Fungal isolates identified from the fruits included Aspergillus niger, Candida krusei, Fusarium oxysporum, Candida sp., A. fumigatus, Penicillium notatum, and A. terreus. The Gas Chromatography-Mass Spectrometry analysis of the beeswax indicated the presence of certain compounds that may contribute to its antimicrobial properties. Conclusion: The findings of this study demonstrate that beeswax emulsion effectively extends the shelf-life of tomato fruits, offering a potential solution to reduce waste and economic losses for farmers and the broader economy.